Population genomic analysis of Cryptococcus Brazilian isolates reveals an African type subclade distribution. Issue 6 (2nd April 2021) - Maufrais, Corinne; de Oliveira, Luciana; Bastos, Rafael W; Moyrand, Frédérique; Reis, Flavia C G; Valero, Clara; Gimenez, Bianca; Josefowicz, Luisa J; Goldman, Gustavo H; Rodrigues, Marcio L; Janbon, Guilhem
Abstract: The genomes of a large number of Cryptococcus neoformans isolates have been sequenced and analyzed in recent years. These genomes have been used to understand the global population structure of this opportunistic pathogen. However, only a small number of South American isolates have been considered in these studies, and the population structure of C. neoformans in this part of the world remains elusive. Here, we analyzed the genomic sequences of 53 Brazilian Cryptococcu s isolates and deciphered the C. neoformans population structure in this country. Our data reveal an African-like structure that suggested repeated intercontinental transports from Africa to South America. We also identified a mutator phenotype in one VNBII Brazilian isolate, exemplifying how fast-evolving isolates can shape the Cryptococcus population structure. Finally, phenotypic analyses revealed wide diversity but not lineage specificity in the expression of classical virulence traits within the set of isolates.